Analisis Behavioral Intention Pada Layanan Aplikasi RCTI+ - Anggit Mardiana Permatasari; Hetty Karunia Tunjungsari (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
The current era is called the information age, where humans really need information. The existence of the internet on smartphones makes it easier for humans to get information and enjoy content wherever and whenever. One of the content services in Indonesia is the MNC Group's RCTI + application. Although RCTI + is a new company, RCTI + has an active number of users of 302,569 until November 2019. RCTI + has a fairly high market share because the digital era is growing rapidly. This study measures the interest of users of RCTI + applications in Indonesia by using a modified UTAUT2 research model, where researchers analyze the variables Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Hedonic Motivation, Habit, and Content on Behavioral Intention. The data used in this study were 89 valid respondents obtained online using a questionnaire. Respondents are users of the RCTI + application. Researchers used Structural Equation Modeling (SEM) with SmartPLS software version 3.0 to test hypotheses. The results showed that Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Habit and Content had an influence on Behavioral Intention. However, Hedonic Motivations has a negative influence on Behavioral Intention. The Age variable as a moderator variable influences Content on Behavioral Intention, while Gender has no effect. This study resulted in an R2 of 0,900 and included in the moderate category. This research, has found that the variable that most influences Behavioral Intention is Habit.